PENGARUH SUHU DAN LAMA THAWING SEMEN BEKU SAPI LEMOUSIN TERHADAP MOTILITAS SPERMATOZOA - Sritiasni; Edi Purwono (Politeknik Pembangunan Pertanian Manokwari, 2016)
This study aims to determine how the cattle frozen semen motility lemousin on temperature and duration of different thawing in Prafi SP I Manokwari District. The method of analysis is a preliminary stage and the stage of implementation. Design of Experiments Experiments were used in this study is 3 x 3 factorial experiment with a completely randomized design basis (RAL). A factor that is thawing temperature 5 0C, 27 0C and 40 0C and factor B long thawing, 5 minutes, 30 minutes and 60 minutes with 3 x replications. The data were processed by analysis of variance procedure and if there is a real difference followed by Duncan's multiple range test. The results showed that the temperature penetitian 5 0C with 5 minutes is the most excellent and worthy for artificial insemination. The benefits of this research is to provide information about the implementation of thawing in accordance with the conditions on the ground, so it can be used as consideration improve the management of the IB program and the achievement of success.